(untitled) (Estudios humanísticos. Geografía, historia y arte, 1992)
Very little scientific research has been done on the Low Imperial period in the Gallaecia province. Our aim is widening our knowledge about this historical time. We will focos on: A revision of classical literary sources. A study of the Economy: monetary treasuries, roadways, ceramic... A study of Society: roman and native onomastics.